2018
DOI: 10.1002/mc.22787
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of CX3CL1 on lung cancer prognosis in smokers and non‐smokers

Abstract: CX3CL1 is a unique chemokine, expressed in both soluble and membrane bound forms, which mediates different biological activities. Recent studies have revealed the potential of CX3CL1 signaling pathway as a target for the treatment of inflammation and cancer. The correlation between expression of CX3CL1 and prognosis of patients varies among cancers. In this study, based on CX3CL1 immunohistochemistry in non-small cell lung cancer, CX3CL1 levels were positively associated with cancer stage (Pearson chi-square, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Studies have shown that the CX3CL1-CX3CR1 axis is up-regulated in breast cancer, colon cancer, gastric cancer, prostate cancer and other malignancies. Tumor cells expressing CX3CL1 can promote the invasion and metastasis of CX3CR1-positive tumor cells [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the CX3CL1-CX3CR1 axis is up-regulated in breast cancer, colon cancer, gastric cancer, prostate cancer and other malignancies. Tumor cells expressing CX3CL1 can promote the invasion and metastasis of CX3CR1-positive tumor cells [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Su et al demonstrated that the CXC3CL1 level showed survival effects in lung adenocarcinoma but not in squamous cell carcinoma (81). The expression of CX3CL1 was found to be increased in lung cancer with higher pathological grades and metastatic lymph nodes (142).…”
Section: Cx3cl1mentioning
confidence: 94%
“…In the entire NSCLC cohort, no correlation between the expression of the protein and clinical course of the disease was observed. Such an unexpected result may be explained by different pathways of carcinogenesis in the smoking and non-smoking patients as well as in SCC and ADC patients (23). High mitotic activity is a known histopathological feature of malignant neoplasms.…”
Section: Revision Of Novel Prognostic Factors In Lung Cancermentioning
confidence: 99%
“…A high level of expression of this protein causes activation of T CD8 + lymphocytes and NK cells within the tumor, which leads to a more effective elimination of the transformed cells (21). A more detailed study into the role of CX3CL1 in the lung tumors revealed that ADC patients with a smoking history and high expression of CX3CL1 had a shorter OS (HR=3.01) (23). Moreover, in the same study, a high CX3CL1 expression in the smoking AD patients happened half as often as in the SCC and ADC non-smoking patients.…”
Section: Revision Of Novel Prognostic Factors In Lung Cancermentioning
confidence: 99%